MODEL SMART CLASSROOM AKTIF UNTUK MENINGKATKAN BELAJAR DAN BERGERAK PADA ANAK SD - Bahar, Awaluddin; Alim, Bahrul (STKIP Subang, 2026)
This study aims to examine the implementation of an Active Smart Classroom model to improve learning outcomes and physical movement activity in elementary school students. This research was conducted using a classroom action research (CAR) approach carried out at SDN 7 Salotungo, Soppeng Regency, South Sulawesi, involving 28 students in grade IV as research subjects. The research procedure was carried out in two cycles, each consisting of planning, implementation, observation, and reflection stages. Data collection techniques include observation, tests, and documentation. Data analysis was conducted using descriptive statistics. The results showed that the implementation of the Active Smart Classroom model significantly improved student learning outcomes, with the average score rising from 61.4 (pre-cycle) to 74.8 (Cycle I) and 87.3 (Cycle II), exceeding the KKM of 75. Physical activity of students also increased significantly, where the percentage of active students rose from 42.8% in the pre-cycle to 71.4% in Cycle I and 89.3% in Cycle II. It is concluded that the Active Smart Classroom model is effective in improving both cognitive learning outcomes and physical movement activity of elementary school students simultaneously